An Aesthetic Exploration and its Embodied Imagination in The Parrot in the Cage - Babu Ram Khanal (Interdisciplinary Journal of Management and Social Sciences, 2022)
This research tries to analyse and interpret the poem The Parrot in the Cage on three different levels. First, it attempts to explore the artistic beauty of the cage where a parrot, a creation of nature, is moving to and fro prattling human language, pausing each time. Second, it attempts to embody the satire on human life that every human being is in chain provided that they are born free. The universe has been delineated as a cage where everyone is in trap. Finally, the cage is sketched as an emblem of confinement, a punishment where people are given the status of others during the tyrannical rule of Ranas. It discloses the injustice, ill attitude and superiority feeling of rulers. The wretchedness and melancholic state of majority of poor people, deprived of education, unemployment and self-respect has been skilfully presented in the text. In addition, the hostile environment created by bourgeoisie Ranas where people were doomed to live like parrot in the cage almost paralyzed has been another focus of the poem which the research endeavours to locate.